Instagram as Digital Communication Tool for the Museums: a Reflection on Prospectives and Opportunities through the Analysis of the Profiles of Louvre Museum and Metropolitan Museum of New York - Zingone, Michela (European Journal of Social Science Education and Research, 2024)
Launched in October 2010, Instagram is nowadays one of the most used social networks. According to the latest data released by the platform in 2018, in fact, the number of active users exceeded one million. From the public to the private sector, several actors have integrated Instagram into their communication plan. Among them, there are also the museum institutions. The object of this article is to look at what types of contents museums usually share and to understand how they are using this innovative communication channel based essentially on images to document, communicate their daily activity, their identity, and get in touch with users. Through the method of the content analysis, we propose a qualitative analysis of the posts published in a period of 30 days on the official profiles of the Louvre Museum in Paris and the Metropolitan Museum of Art in New York.